Economic Implications of Job Instability: A Case Study at the National University of Costa Rica - Rodríguez Soto, Maritza (2019)
This article addresses, through the stories of the population hired on an interimbasis at the National University of Costa Rica, the economic implicationsthat are the result of this working condition; such as: constant delays in theappointment and delays in the deposit of the salary, which have an impact onthe payment of the monthly family expenses, report of rates in the pensionsystem, count of the working time served; among others.The economic implications of interinazgo are reflected in the family and personalenvironment; reason why survival strategies are used to face economiccommitments. While in the workplace it affects the ability to focus on the task for which they have been hired, due to their constant economic concerns, and instability associated with the interinazgo, while much of their energy, time and attention is invested in the economic survival The words of the interviewed population show feelings of fear in the face of labor and economic instability that limits the plans to the future and therefore the concretion of these; Therefore, institutional policy and university bodies must develop mechanisms that favor the working conditions of this population.